2011
DOI: 10.2499/capriwp99
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Assets, and Agricultural Development Programs: A Conceptual Framework

Abstract: Being able to access, control, and own productive assets such as land, labor, finance, and social capital enables people to create stable and productive lives. Yet relatively little is known about how agricultural development programs can most effectively deliver these outcomes of well-being, empowerment, and higher income in a way that acknowledges differential access to and control over assets by men and women. After reviewing the literature on gender and assets, this paper offers a conceptual framework for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…It was observed that poor involvement of youth cause difficulty in agricultural system (Jothilakshmi et al, 2013) and necessitates condition to improvise the situation. The ability to control nearby resources empowers farming communities and it is appropriate to identify different approaches effective agricultural productivity (Meinzen-Dick et al, 2011). It includes features of technologies that reduce cost of production and enable farmers to take less risk so as to cope with farm intensification (Aune & Bationo, 2008).…”
Section: Technological Requirement(s) In Agricultural Systemmentioning
confidence: 99%
“…It was observed that poor involvement of youth cause difficulty in agricultural system (Jothilakshmi et al, 2013) and necessitates condition to improvise the situation. The ability to control nearby resources empowers farming communities and it is appropriate to identify different approaches effective agricultural productivity (Meinzen-Dick et al, 2011). It includes features of technologies that reduce cost of production and enable farmers to take less risk so as to cope with farm intensification (Aune & Bationo, 2008).…”
Section: Technological Requirement(s) In Agricultural Systemmentioning
confidence: 99%
“…household members, second wife and/or family, extended family, lover), based on a mixture of their own and others' interests, or based on their own selfinterest. Thus, Ugandan smallholder pig-farming households cannot be viewed as one entity with a single set of preferences nor as multiple individuals operating solely in their own best interest, just as other authors have cautioned [4,[6][7][8].…”
Section: Income Allocation and Beneficiariesmentioning
confidence: 99%
“…Household members may have differing preferences and abilities to impact intra-household decision-making outcomes [4,7,8]. Agency, "the ability to define one's goals and act upon them" for example through decisionmaking, and gaining, retaining, and exercising command over goods and income [9] may differ between members of the same household.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations